Pemberdayaan Masyarakat Melalui Diversifikasi Produk Ikan Puri (Stolephorus sp.) - Ernawati Ernawati; Intanurfemi B. Hismayasari; Astervina W. Puspitasari; Ismail Ismail; Muhammad Ali Ulat; Hendra Poltak (Buletin SWIMP, 2021)
This activity aims to assist and provide training to the Victor Jaya fishing group community about the diversification of Anchovy fish in order to increase its economic value. This activity comprised 25 people, including 11 fishermen, 3 entrepreneurs, and 11 fisherman's wives, In the manufacture of anchovy sauce, raw materials are red chili, garlic, shallots, shrimp paste and dried puri fish. The method of implementation is through training and direct practical assistance. People have different tastes in spicy chili products, according to the training findings, with 54 percent preferring extremely spicy, 33 percent preferring spicy, and 8% preferring not spicy. The outcomes of the chili processing training, on the other hand, produced a tasty product that can be preserved for a long time and is well received by the general public.